Estudo do desalinhamento entre os eixos de anisotropia via magnetorresistência anisotrópica em sistemas com exchange bias - Siqueira, Junara Villanova de (2019)
The Exchange Bias effect (EB) arises in systems with interfacial coupling, generally between a ferromagnetic (FM) and a antiferromagnetic (AFM) material. The well-known manifestations of this phenomenon are the field shift in the magnetization curves and the increase in the coercive field when compared to the uncoupled FM material. In this work, the study of this interfacial coupling between the FM (NiFe) and the AFM (FeMn) material has been performed through the structural, magnetic and eletric transport characterization. NiFe/FeMn films were grown by varying the argon pressure during the deposition of the FM layer and, subsequently, NiFe/FeMn films were grown by varying the pressure of the both layers during the deposition. These were made in order to improve the (111) texture of NiFe and FeMn layers, as well as to improve interface quality and thus to obtain a system with a better defined uniaxial and unidirectional anisotropies. We have used masks during deposition in order to define the direction of the electric current with relation to the anistropy direction in the anisotropic magnetoresistence measurements (AMR). After concluding that the best Ar pressure value was 1,5 mTorr, two sets of samples were produced, one of them with varying FM layer thickness and the other one by changing the thickness of the AFM layers. Samples with the thinner FM layer thickness were also to verify if it would be possible to observe the rotational hysteresis by AMR. The films were grown on glass substrates by magnetrom sputtering . The electrical transport measurements were measured in the system implemented in the Laboratório de Magnetismo e Materiais magnéticos for AMR measurements as a function of the field angle. By compariparing the experimental data to calculated ones, we have obtained the magnetic parameters describing the systems.